'The Librarian as Historian': Hugh Wright, C. H. Bertie and Their Circle. Issue 1 (2nd January 2018) - Whitaker, Anne-Maree
Abstract: 'The Librarian as Historian' was the title of an article written in 1902 by the first Mitchell Librarian, Hugh Wright (1909–1932). His 'old friend' Charles Henry Bertie was inaugural Sydney Municipal Librarian (1909–1939), and the two worked with other librarian historians in a range of endeavours over several decades. While Bertie has an entry in the Australian Dictionary of Biography, Wright was overlooked and remains without a biographical study. This paper builds on fundamental biographical research on the two men as a basis for an examination of their careers as librarians, historians and collaborators. Both men wrote and lectured on Australian history in public forums, as well as collecting, cataloguing and providing access to material for other historians. From its beginnings the Mitchell Library under Wright searched Britain and Europe for manuscripts and books, and soon became the leading research centre for the study of the history of Australia and the Pacific. Bertie's influence extended well beyond the Municipality of Sydney through his extensive journalism and his involvement in the 1938 Australian Sesquicentenary Historical Exhibition. The legacy of this circle is still a strong influence on public versions of Australia's national narrative.